COLLABORATIVE GOVERNANCE IN REALIZING SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN CIBIRU WETAN VILLAGE CILEUNYI DISTRICT BANDUNG REGENCY - Saputri, Riska; Rohayatin, Titin; Fauzi, Lukman Munawar (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
The title of this thesis is "Collaborative Governance in Achieving Sustainable Development Goals (SDGs) in Cibiru Wetan Village, Cileunyi District, Bandung Regency". This research is motivated by the less than optimal implementation of collaborative governance in increasing village economic growth, this incated by the lack of community participation, the complexity of survey instruments, the lack of maximum communication by the village government regarding the concept of SDGs, the lack of all stakeholders understanding their roles and responsibilities, and the collaboration process is not fully inclusive and synergistic. Problem formulation: how Collaborative Governance in realizing the SDGs as a pillar of economic growth. Research objective: to describe and analyze the implementation of cross-sectoral collaboration in sustainable village development. The theory used by Ansell and Gash, which includes four dimensions: starting conditions, institutional design, facilitative leadership and collaborative processes. A descriptive research method with a qualitative approach was employed. Data collection techniques through literature studies and field studies (observation, interviews, and documentation). Research informants: consists of five pentahelix elements, including village governments, communities, the private sector, academics and the media. The results show: (1) the initial conditions faced with resource gaps, low digital literacy, and lack of public understanding of the SDGs, (2) institutional design is seen through formal-informal regulations, but it has not been accompanied by a comprehensive understanding between stakeholders, (3) facilitative leadership can be seen from the active role of village heads in building communication and trust. (4) The collaboration process is carried out through a deliberative forum.